Cased-based education rounds—the eternal heart of an international training program - Breatnach, Colm R.; Floh, Alejandro; Hamilton, Melanie; Mema, Briseida (Frontiers in Pediatrics, 2024)
Case-based teaching or "Morning Rounds" have been used in medical education for more than a century and remain a cornerstone for teaching in many training programs. Our Pediatric Critical Care Medicine (PCCM) program was established forty years ago and has retained this form of teaching since its inception. Case-based rounds have consistently had the highest evaluation of all curricula in our program. Here we review the history of how these rounds were introduced in medical education, provide data from the learners' evaluation of these case-based rounds, and discuss the strengths and potential drawbacks of this form of teaching from an educational theories perspective with the hope that they can be used by other Pediatric Critical Care training programs.